(untitled) (Dhaka University Journal of Biological Sciences, 2025)
Salad vegetables are widely eaten raw in Bangladesh because of their high nutritional content and health benefits. However, contamination of salad vegetables with parasites poses a significant health risk. This study aimed to document the parasitic contamination of raw salad vegetables sold in local markets of Dhaka and the role of vendors’ hygiene practices in transmitting parasitic pathogens. 29.6% of the salad vegetables were contaminated with 8 different parasites. Ascaris sp. (20.4%) > Entamoeba sp. (13.0%) > Hymenolepis sp. (11.1%) > Cystoisospora sp. (5.6%) >Hookworm (3.7%), Trichuris trichiura (3.7%) > Taenia sp. (2.8%). Leafy vegetables (coriander 66.7%, mint 44.4%, lettuce 38.9%) were more contaminated than nonleafy vegetables (carrot 11.1%, Tomato 11.1%, cucumber 5.6%). The vendors’ hygiene practices: the habit of washing hands with soap and nail status, and infected vendors were proved to be the statistically significant contributing sources of observed parasitic contamination. The present study demonstrated the presence of infective stages of different pathogenic parasites on the surface of raw salad vegetables. It establishes a relationship between vendors’ hygiene practices and parasite transmission. Eating them may spread vegetable-borne diseases in Dhaka unless adequately cleaned and disinfected prior to consumption. Dhaka Univ. J. Biol. Sci. 34(1): 51-62, 2025 (January)